Application of abdominal ultrasonography in surgical necrotizing enterocolitis: a retrospective study - Chen, Qin; Yao, Weiquan; Xu, Fengdan; Liao, Jinfeng; Li, Jinfeng; Mai, Minling; Xie, Haoqiang; He, Xiaoguang; Li, Ning (Frontiers in Microbiology, 2023)
Background Necrotizing enterocolitis (NEC) is a severe inflammatory bowel disease that may lead to perforation, causing high morbidity and mortality in preterm infants. Abdominal ultrasound (AUS) has shown benefits in diagnosing and managing NEC in recent years. Objective This paper focused on the utility of AUS in the diagnosis and evaluation of surgical NEC. Patients and methods In this retrospective study, available data of the patients diagnosed from January 2019 to June 2022 were reviewed. Sensitivity and specificity of AUS in diagnosing a perforation were analyzed. Typical cases for application of AUS in monitoring and evaluating progression, complications, and sequela of NEC were described. Results There were 69 neonates diagnosed with NEC and examined by AUS, of whom 8 patients developed a perforation. AUS was used for diagnosing a perforation in 8 patients with key features of pneumoperitoneum and/or complex ascites, allowing to find four locations of perforation, with the sensitivity and specificity of 100%. Conclusion AUS plays an important role in diagnosing and evaluating surgical NEC in newborn infants with good sensitivity and specificity.